Faktor-Faktor Yang Mempengaruhi Kualitas Sumberdaya Manusia Dan Perekonomian Kabupaten/Kota Di Provinsi Jambi - Munawwaroh, Munawwaroh; Amar, Syamsul; Idris, Idris (Program Studi Magister Ilmu Ekonomi, 2013)
This article focus to analyze (1) Effect of education budget, health budget and economy toword of human resources quality in Jambi province. (2) The influence of inflation, unemployment and human resources quality toword of economy in Jambi province. The data poaltime series was taken 2007-2011 of regency and city in Jambi province. The analyze use Simultaneous model. Before analysis, we also checked cointegration test and causalities between human resources quality and economy. The result of research concludes that (1) The Â have education budget a significant and positive impact toword of human resources quality, health budget have a unsignificant and positive impact toword of human resources quality and economy have unsignificant and positive toword of human resources in Jambi province. (2) Inflation have significant and negative impact toword of economy, unemployment and human resources quality unsignificantly influence impact toword economy in Jambi province. Policy implications of the results of this study are: 1) government efforts through education budget and health budgetÂ in the form of the government budget through health and education facilities in the form of facilities and infrastructure, as well as education and health services to improve the quality of human resources. 2) efforts to do next government in building the economy of the region is to maintain stable prices in the market to curb inflation and provide employment business for the community as well as providing training to workers in order to reduce unemployment. Keywords: Human resources quality, economics, education budget, health budget, education level, inflation and unemployment.